Hubungan Antara Tingkat Pendapatan Masyarakat dengan Kejahatan Penyerobotan Tanah Negara dan Kerusakan Hutan di Kelurahan Manutapen Kecamatan Alak Kota Kupang: The Relationship Between Community Income Levels and Crimes of Invading State Land and Forest Damage in Manutapen Village, Alak District, Kupang City - Charles Banoet; Fransina Pattiruhu (Warkat, 2022)
Land is a gift from God Almighty to mankind on earth. Tanak raids, whether intentional or unintentional, in Indonesia in general and especially in Kupang City, NTT, specifically in Manutapen Village, Alak District, also attract the attention of many people. Specifically related to cases of state land grabbing that occurred in the teak forest area in Manutapen Subdistrict, historically this has occurred since 1985. Weak supervision from the relevant agencies that have a direct interest in state forest areas, is one of the factors that causes/triggers cases of state land grabbing. which has an impact on environmental damage to the forest (teak) area in Manutapen Village, Alak District, Kupang City.